Immunopathogenesis of recurrent vulvovaginal candidiasis. - Fidel, P L (1996)
Recurrent vulvovaginal candidiasis (RVVC) is a prevalent opportunistic mucosal infection, caused predominantly by Candida albicans, which affects a significant number of otherwise healthy women of childbearing age. Since there are no known exogenous predisposing factors to explain the incidence of symptomatic vaginitis in most women with idiopathic RVVC, it has been postulated that these particular women suffer from an immunological abnormality that prediposes them to RVVC. Because of the increased incidence of mucosal candidiasis in individuals with depressed cell-mediated immunity (CMI), defects in CMI are viewed as a possible explanation for RVVC. In this review, we attempt to place into perspective the accumulated information regarding the immunopathogenesis of RVVC, as well as to provide new immunological perspectives and hypotheses regarding potential immunological deficiencies that may predispose to RVVC and potentially other mucosal infections by the same organism. The results of both clinical studies and studies in an animal model of experimental vaginitis suggest that systemic CMI may not be the predominant host defense mechanism against C. albicans vaginal infections. Rather, locally acquired mucosal immunity, distinct from that in the peripheral circulation, is now under consideration as an important host defense at the vaginal mucosa, as well as the notion that changes in local CMI mechanism(s) may predispose to RVVC.